Building a Live Cell Microscope: What You Need and How to Do It. Issue 1 (15th July 2013) - Watkins, Simon C.; St. Croix, Claudette M.
Abstract: In this post‐genomic era, the predominant focus of biomedical research has moved towards elucidating the functionality of molecules at the cellular and subcellular level in integrated living systems. As such, biologic imaging has moved beyond the collection of static "snapshots" of the cellular state to the real‐time visualization of cellular and molecular behavior in three‐dimensional (3D) space. Live‐cell imaging techniques can be used to assess protein abundance, as well as determine the functional role(s) and interactions of multiple unique molecules concurrently within the cellular environment, and determine the effects of these molecules on cell development, organization, and fate over extended periods of time. Such studies require advanced systems that allow multiparametric analysis of cells while maintaining their functional viability. This unit will focus on the design and implementation of modern live‐cell imaging systems. We will examine the principle problems facing live‐cell microscopists including: focus drift, cell viability, photo‐toxicity, and data acquisition, and suggest appropriate solutions to these issues. Our goal in this unit is to provide individual scientists with the information required to implement live‐cell imaging solutions within their own laboratories. Curr. Protoc. Cytom . 65:2.21.1‐2.21.10. © 2013 by John Wiley & Sons, Inc.